Pengaruh Penggunaan Iklan Televisi dan Daya Tarik Iklan terhadap Brand Equity Shampo Head & Shoulders - Lorenza, Vegent; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
As part of the P&G family, Head & Shoulders shampoo has been trusted as shampoo no. 1 world#. One of the efforts to maintain this existence Head & Shoulders issued a television commercial that is interesting, and different. The appeal of an advertisement and advertising media can be a means to introduce a product and one that must be considered to create brand equity. This study aims to find and determine the effect of the use of television advertising and advertising attractiveness on the brand equity of Head & Shoulders shampoo. The researcher uses brand equity, television advertising, and advertising appeal as research concepts. Using a quantitative approach and survey methods. The population used is respondents who have watched television advertisements for Head & Shoulders shampoo and have used Head & Shoulders shampoo products. The data obtained were analyzed using t test, normality, multiple regression..linear.test, looking for the coefficient of determination, validity test, and reliability test. The t-test showed a significant effect, meaning that television advertising and advertising appeal had a significant effect on the brand equity of Head & Shoulders shampoo. Sebagai bagian dari keluarga P&G, shampo Head & Shoulders telah dipercaya sebagai shampo no. 1 dunia#. Salah satu upaya untuk mempertahankan eksistensi ini Head & Shoulders mengeluarkan iklan televisi yang menarik, dan berbeda. Daya tarik sebuah iklan dan media iklan dapat menjadi sarana untuk memperkenalkan suatu produk dan salah satu yang harus diperhatikan untuk menciptakan ekuitas merek. Penelitian bertujuan untuk mencari dan mengetahui pengaruh penggunaan iklan televisi dan daya tarik iklan terhadap ekuitas merek shampo Head & Shoulders. Peneliti menggunakan ekuitas merek, iklan televisi, dan daya tarik iklan sebagai konsep penelitian. Menggunakan pendekatan kuantitatif serta metode survei. Populasi yang dipakai adalah responden yang pernah menonton iklan televisi shampo Head & Shoulders dan pernah menggunakan produk shampo Head & Shoulders. Data yang diperoleh dianalisis menggunakan uji t, normalitas, pengujian..regresi..linier.berganda, mencari koefisien determinasi, uji validitas, dan uji reliabilitas. Uji t menunjukkan pengaruh yang signifikan, artinya iklan televisi dan daya tarik iklan berpengaruh signifikan terhadap ekuitas merek shampo Head & Shoulders.